Der Kolosserhymnus Untersuchungen zu Form, traditionsgeschichtlichem Hintergrund und Aussage von Kol 1,15-20 - Stettler, Christian (Mohr Siebeck, 2019)
Christian Stettler attempts a new way of interpreting the hymns in Col 1:15-20. Starting from its Judeo-Christian backdrop he analyses the form of the text against the background of the Psalm literature found in the Old Testament and early Jewish writings and interprets the text against the background of Old Testament and early Jewish traditions. Christian Stettler shows the development of the whole complexes of traditions which are responsible for the Colossian hymn. It becomes evident that Col 1:15-20 - an implicit christological midrash - is a concise and organic entity which can be interpreted without assuming additions to an original text. In early Jewish Wisdom theology most of the traditions which stand behind the hymn are already connected, but only the life, death and resurrection of Jesus made the formulation of the present hymn possible.